Learning Style Preferences of Students Studying in Foreign Language - UĞURAL, MEHMET NURETTİN (My University, 2018)
Knowledge of learning styles plays a vital role in education because, it can enhance the ability of educators to build on student experiences and construct new learning opportunities. This study aimed to understand the learning preferences of students from two distinguishing departments of construction who are educated in foreign language of English. With this aim, following an in depth literature review, the learning style of 170 undergraduate architecture and civil engineering students at Istanbul Technical University were empirically surveyed, using Honey and Mumford’s Learning Style Questionnaire (LSQ). According to statistical tests of the questionnaire data, there is no evidence supporting the hypothetical two bipolar structure of the LSQ. However, the results confirmed different characteristics of students from different disciplines.
Keywords: Learning Style Preference; Architecture Student; Civil Engineering Student; Undergraduate Level